Regulation of MVM NS1 by protein kinase C: Impact of mutagenesis at consensus phosphorylation sites on replicative functions and cytopathic effects - Corbau, Romuald; Rommelaere, Jean; Nüesch, Jürg P. F. (Virology, 2002)
Minute virus of mice NS1, an 83-kDa mainly nuclear phosphoprotein, is the only viral nonstructural protein required in all cell types and it is involved in multiple processes necessary for virus propagation. The diversity of functions assigned to NS1, together with the variation of its complex phosphorylation pattern during infection, suggested that the various activities of NS1 could be regulated by distinct phosphorylation events. So far, it has been demonstrated that NS1 replicative functions, in particular, DNA-unwinding activities, are regulated by protein kinase C (PKC), as exemplified by the modulation of NS1 helicase activity by PKCλ phosphorylation. In order to determine further impact of phosphorylation on NS1 functions, including the induction of cytopathic effects, a mutational approach was pursued in order to produce NS1 variants harboring amino acid substitutions at candidate PKC target residues. Besides the determination of two additional in vivo phosphorylation sites in NS1, this mutagenesis allowed the segregation of distinct NS1 functions from one another, generating NS1 variants with a distinct activity profile. Thus, we obtained NS1 mutants that were fully proficient for trans activation of the viral P38 promoter, while being impaired in their replicative functions. Moreover, the alterations of specific PKC phosphorylation sites gave rise to NS1 polypeptides that exerted reduced cytotoxicity, leading to sustained gene expression, while keeping functions necessary for progeny virus production, i.e., viral DNA replication and activation of the capsid gene promoter. These data suggested that in the course of a viral infection, NS1 may undergo a shift from productive to cytotoxic functions as a result of a phosphorylation-dependent regulation.
Elektronische Reproduktion der Druckausgabe
Gesehen am 15.02.2021